Conflict and Post-Conflict Governance in the Middle East and Africa - Elayah, Moosa A.; Lambert, Laurent A. (Cham : Springer Nature Switzerland : Imprint: Palgrave Macmillan, 2023)
"The book deals with a critical and a timely issue: public policies in the aftermath of civil wars and armed conflicts. Elayah and his team provide a fascinating analysis that represents an excellent resource for policymakers, practitioners, researchers and graduate students working on the Middle East and Africa." - Omar Ashour is Professor of Security and Military Studies at the Doha Institute for Graduate Studies. This book explores the challenges of the governance and public policy in the midst and after conflicts, revolutions, and civil wars in the Middle East and Africa. As anywhere else, the task of rebuilding peace and institutionalizing stability in countries experiencing conflict or just emerging from it, is daunting, uncertain and context specific. Yet, focusing on the Middle East and Africa is of particular relevance, as these two regions feature the highest numbers of inter- and intra-state conflicts, and the central states are more often contested than in the rest of world regions. The book proposes different cases addressing the fundamental challenge of inclusion and cohesion as well as the recurring issue of exclusion in conflict-affected situations. It also offers more theoretical insights and proposed pathways to develop more inclusive and peaceful governance settings in Africa, the Middle East and beyond. It deploys different lenses of social sciences, public policy, and international relations, but also benefits other disciplines that enable a more comprehensive understanding of the multifaceted, complex and dynamic issues at play. Dr. Moosa A. Elayah is Assistant Professor in Public Administration, specialized in Conflict Studies, Peacebuilding, and International Development, at the Doha Institute for Graduate Studies, Qatar. Dr. Laurent A. Lambert is Assistant Professor in Public Policy, specialized in energy policy and climate change politics, at the Doha Institute for Graduate Studies, Qatar.
1. Introduction -- 2. The Role of Sazman-e- Honari Rosanai Oax (Owj) during the "Maximum Pressure" Campaign against Iran -- 3. Seeing Like a State: The Crisis of Building the State of South Sudan -- 4. Policing coexistence through economic incentives: an analysis of Nir Barkat's policies on education in East Jerusalem during his tenure as mayor (2009-2018) -- 5. An exploration of the dimensions of exclusion associated with intimate violence among Syrian refugees in Lebanon, etc.
Keywords: International relations; Middle East -- Politics and government; International Relations Theory; Middle Eastern Politics